Chemical Modification of Phage‐Displayed Helix‐Loop‐Helix Peptides to Construct Kinase‐Focused Libraries. (19th October 2021) - Fujiwara, Daisuke; Mihara, Kousuke; Takayama, Ryo; Nakamura, Yusuke; Ueda, Mitsuhiro; Tsumuraya, Takeshi; Fujii, Ikuo
Abstract: Conformationally constrained peptides hold promise as molecular tools in chemical biology and as a new modality in drug discovery. The construction and screening of a target‐focused library could be a promising approach for the generation of de novo ligands or inhibitors against target proteins. Here, we have prepared a protein kinase‐focused library by chemically modifying helix‐loop‐helix (HLH) peptides displayed on phage and subsequently tethered to adenosine. The library was screened against aurora kinase A (AurA). The selected HLH peptide Bip ‐3 retained the α‐helical structure and bound to AurA with a K D value of 13.7 μM. Bip ‐3 and the adenosine‐tethered peptide Bip ‐3 ‐Adc provided IC50 values of 103 μM and 7.7 μM, respectively, suggesting that Bip ‐3 ‐Adc bivalently inhibited AurA. In addition, the selectivity of Bip ‐3 ‐Adc to several protein kinases was tested, and was highest against AurA. These results demonstrate that chemical modification can enable the construction of a kinase‐focused library of phage‐displayed HLH peptides. Abstract : Expanding helix‐loop‐helix (HLH) peptide libraries : A phage‐displayed HLH peptide library was chemically modified with adenosine as an anchor molecule for binding to the ATP binding site of protein kinase. This approach to the construction of target‐focused HLH peptide libraries would enable the efficient generation of selective inhibitors not only for protein kinases, but also for other proteins of interest.